1990
DOI: 10.1071/ar9900827
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stripe rust on the quality of Australian wheat varieties

Abstract: The effect of stripe rust on the processing quality of Australian wheat varieties was examined over a four year period. Each year in field experiments, stripe rust was allowed to develop naturally on one half of each plot block while the other was kept disease free using three weekly applications of fungicide. Changes in grain quality were observed with susceptible varieties when subjected to an epiphytotic of the disease. Stripe rust caused kernels to be shrivelled, which resulted in reduced test weight and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…In addition to the yield losses, seeds harvested from fungicide unsprayed plots were shrivelled shape and size that will affect crop establishment of next generation and less plump and low stored food reserve for the next round of crop growth [ Figure 1]. The present investigations are in line with the work done by [31][32] who discussed that stripe rust has effect on the end use of an already diminished yield for processing due to the changes in shape and size of the grain.…”
Section: Seed Quality Losssupporting
confidence: 88%
“…In addition to the yield losses, seeds harvested from fungicide unsprayed plots were shrivelled shape and size that will affect crop establishment of next generation and less plump and low stored food reserve for the next round of crop growth [ Figure 1]. The present investigations are in line with the work done by [31][32] who discussed that stripe rust has effect on the end use of an already diminished yield for processing due to the changes in shape and size of the grain.…”
Section: Seed Quality Losssupporting
confidence: 88%
“…On the other hand, the effect of biotrophic pathogens in dough rheology is not as consistent or as marked as that observed on GPC, and the magnitude and direction of those effects have been understood less clearly. It has also been reported that under P. triticina artificial inoculations, the alveogram parameter AlvP was more decreased than AlvL, resulting in a minor AlvP/L ratio (Fleitas et al, 2018b;Rozo Ortega, 2019), and loaf volume was also affected (Fleitas et al, 2018b). O'Brien et al (1990 reported that under P. striiformis epidemics, the dough development time from the farinograph (FarB) was shorter and mixing tolerance and extensograph maximum resistance were lower for susceptible varieties, whereas the loaf volume was not affected.…”
Section: Effect Of Foliar Diseases Caused By Biotrophs On Processing mentioning
confidence: 88%
“…Although the tendency of the impact of biotrophic pathogens is clearly toward a decrease in GPC as N is generally more affected than assimilated carbohydrates, some controversial results have been reported. O'Brien et al (1990) documented that when P. striiformis was predominant, GPC increased due to the concentration effect generated by shriveled grains and Matzen et al (2019) under natural infections generated by Z. tritici, P. striiformis, and B. graminis found that disease control reduced GPC, also due to a dilution effect. Furthermore, different responses depending on the genotype have been found (Everts et al, 2001;Buendía-Ayala et al, 2019), sometimes varying with the resistance level (Conner et al, 2003).…”
Section: Effect Of Foliar Diseases Caused By Biotrophs On Processing mentioning
confidence: 99%
See 1 more Smart Citation
“…On treated plots, Hectolitre weight varied from 70.7 kghl -1 on the moderately susceptible to 73.4kghl -1 the resistant varieties. [40] suggested that shrivelling of wheat kernels reduces flour yield and the work of [41] indicated that stripe rust affected grains resulted in lower dough strength (the physical strength to resist extension), which in turn, could affect baking quality.…”
Section: Discussionmentioning
confidence: 99%